Acceptance of a pre-visit intervention to engage teens in pediatric asthma visits. Issue 11 (November 2017) - Sleath, Betsy; Carpenter, Delesha M.; Davis, Scott A.; Watson, Claire Hayes; Lee, Charles; Loughlin, Ceila E.; Garcia, Nacire; Etheridge, Dana; Rivera-Duchesne, Laura; Reuland, Daniel S.; Batey, Karolyne; Duchesne, Cristina; et al.
Highlights: Almost 95% of teens recommended the educational video for other teens. Non-White teens were more likely to find the question prompt list and video more useful than White teens. Providers should consider having teens complete asthma question prompt lists during pre-visit wait times. Providers should consider having teens watch the educational video with parents during pre-visit wait-times. Abstract: Objective: The objectives of this study were to: (a) describe teen feedback on an asthma question prompt list/video intervention designed to motivate teens to be more engaged during visits and (b) examine teen demographics associated with teen acceptance of the intervention. Methods: Two hundred and fifty-nine teens ages 11 to 17 with persistent asthma were enrolled into a randomized, controlled trial and assigned to either a standard care or an intervention group where they watched an educational video with their parents and received a prompt list to complete before visits. Teens were interviewed after visits. Results: Of the 185 teens randomized to the intervention group: 93% said teens should complete the prompt lists before visits; 95% recommended teens should watch the video before visits; teens with moderate/severe persistent asthma were significantly more likely to find the prompt list useful; non-White teens were significantly more likely to find the prompt list and video more useful. Conclusions: Teens exposed to the question prompt list/video had very positive feedback about the intervention. Practice implications: Providers/practices should consider having teens complete question prompt lists during pre-visit wait time for use during visits and watch the video with their parents before visits.